Optimalisasi Pengelolaan Keuangan UMKM Melalui Pelatihan Dan Mentoring - Kurniawan, Kurniawan (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, contributing more than 60% to the GDP and absorbing more than 90% of the workforce. However, MSMEs often face challenges in financial management, especially in preparing financial reports in accordance with accounting standards. The main problems faced by MSMEs include lack of accounting knowledge, limited time and resources, complexity of accounting material, lack of continuous mentoring, and inability to use financial technology. To address these issues, this community service activity designs a solution in the form of intensive training with simplified materials, mentoring by financial mentors or consultants, the use of user-friendly financial applications, practical skills training, as well as regular evaluation and feedback. This activity utilizes practical learning methods and intensive mentoring, including intensive training, mentorship, periodic evaluation, and the use of technology. The target participants are MSME actors in Mojokerto City who have participated in previous training programs but still struggle with implementing accounting practices. The results achieved in this activity include the preparation of systematic and applicable training materials, the creation of a specialized Excel accounting application for MSMEs, testing of the application, participant forums, as well as training and mentoring for MSME participants. The next stages of the plan include monitoring and evaluation, continued mentoring activities, specific and advanced training, network building and collaboration, as well as further research and information dissemination. It is expected that this community service program will have a significant impact on the development of MSMEs in Mojokerto City and create a more sustainable and inclusive business ecosystem.